Indoor Wave Propagation Prediction for Corridors Segments with Partially Reflecting Walls by Using 3D Waveguide Modal Analysis - El-Maghrabi, Hany M.; Attiya, Ahmed M.; Hashish, Essam A. (Applied Computational Electromagnetics Society Journal (ACES), 2021)
In this paper, a model is presented to simulate wave propagation in indoor corridors with partially reflecting walls. The model is based on combination of modal analysis, dyadic Green’s function, mode matching method and generalized scattering matrix. A new approach to simulate the effect of partial reflectivity of the walls of the waveguide model is proposed. This approach is based on approximating the fields inside the space of the actual waveguide section by equivalent waveguide sections of larger dimensions with PEC (Perfect Electric Conductor) walls. A simple scenario is considered in order to check the accuracy of this model. This scenario is verified by comparing experimental and numerical simulation results. The obtained results show that the proposed model is suitable for predicting accurate electric field strength due to an electromagnetic source in an indoor environment with partially reflecting boundaries.